Biological Roles of Lipocalins in Chemical Communication, Reproduction, and Regulation of Microbiota - Stopková, Romana; Otčenášková, Tereza; Matějková, Tereza; Kuntová, Barbora; Stopka, Pavel (Frontiers in Physiology, 2021)
Major evolutionary transitions were always accompanied by genetic remodelling of phenotypic traits. For example, the vertebrate transition from water to land was accompanied by rapid evolution of olfactory receptors and by the expansion of genes encoding lipocalins, which – due to their transporting functions – represent an important interface between the external and internal organic world of an individual and also within an individual. Similarly, some lipocalin genes were lost along other genes when this transition went in the opposite direction leading, for example, to cetaceans. In terrestrial vertebrates, lipocalins are involved in the transport of lipophilic substances, chemical signalling, odour reception, antimicrobial defence and background odour clearance during ventilation. Many ancestral lipocalins have clear physiological functions across the vertebrate taxa while many other have – due to pleiotropic effects of their genes – multiple or complementary functions within the body homeostasis and development. The aim of this review is to deconstruct the physiological functions of lipocalins in light of current OMICs techniques. We concentrated on major findings in the house mouse in comparison to other model taxa (e.g. voles, humans, birds) in which all or most coding genes within their genomes were repeatedly sequenced and their annotations are sufficiently informative.